A comprehensive study of potassium nutrition in Theobroma cacao L. : morphophysiological, biochemical, and genetic insights (2024)
ABSTRACT: Climate change is causing global crop yield losses, emphasizing the need for new solutions to ensure food security in suboptimal environments. One potential approach is developing genotypes tolerant to potassium (K) nutrient deficiency for agriculturally important crops. However, limited progress has been made in developing genotypes with high potassium use efficiency (KUE). This is likely due to the complexity of the adaptation mechanisms that plants use to tolerate low K conditions, which are influenced by genotype-specific responses and environmental factors. For example, the characterization and development of K-efficient genotypes in cacao crops (T. cacao) remain almost unexplored. Given this scenario, our research used a multidisciplinary approach to understand the morphophysiological, biochemical, and molecular mechanisms underlying the response of T. cacao to different K regimes and identify potential genotypes with higher KUE. This also included developing transgenic tools to test the functionality of candidate genes for future breeding programs in T. cacao. First, we characterized seven T. cacao genotypes (FEAR5, IMC67, CAU39, FSV85, FSV89, CCN51, and FSV41) for their ability to grow under different K concentrations (0, 0.04, 0.4, and 4 mM). We correlated multiple parameters related to biomass and macronutrient distribution as well as photosynthetic performance. Based on high root proliferation, leaf biomass accumulation, maintenance of leaf N accumulation, and proper functioning of photosynthetic processes, we identified two potential contrasting T. cacao genotypes: FEAR5 (tolerant) and IMC67 (sensitive) to low K. Next, we explored their morphophysiological, biochemical, and molecular responses to sufficient (4 mM) and deficient (0 mM) K conditions to understand the adaptation mechanisms in these genotypes under K deficiency. Our results show that FEAR5 is more tolerant to K deficiency compared to IMC67, as evidenced by its superior growth and better photosynthetic activity. Additionally, the enzymatic activities of antioxidant enzymes (CAT, GR and APX) and carbon-related respiratory enzymes (G6PDH, NAD-GAPDH, MDH, ICDH, PK, PEPase) suggest higher sensitivity of IMC67 to altered cellular oxidative environments and carbon flow for primary metabolism. Finally, an RNA-seq analysis was conducted in the roots of FEAR5 and IMC67 genotypes, grown under both K conditions. We identified 1009 differentially expressed genes (DEGs), with 341 and 136 up-regulated and 503 and 109 down-regulated in FEAR5 and IMC67, respectively. The DEGs included diverse gene families such as ion transporters, C/N enzymes, hormones, signaling pathways, and transcription factors, which play a pivotal role in the adaptation of T. cacao to K deficiency, particularly in contributing to higher KUE in the tolerant genotype (FEAR5). These findings also reveal potential candidate genes for use in T. cacao breeding programs to improve KUE. Finally, we aimed to develop transgenic tools for the functional characterization of target genes through an Agrobacterium-mediated transformation process in somatic embryos of T. cacao. Testing the effect of different parameters, the results demonstrate a positive effect of sonication and the activation medium on the transient transformation rate, achieving up to 70-80%. The best results were obtained with the pGH00.0126 vector and the cotyledon segments of embryos in intermediate and late cotyledon stages. However, stable expression was much lower, between 1 and 2 %. Thus, we provide an effective protocol for conducting transient expression studies and functional characterization of target genes in embryogenic somatic tissues. This also encourages further optimization of the transformation process, particularly to increase the stable expression of agronomically important traits in regenerated transgenic cacao plants.